Over a million students use our free study notes to help them with their homework
Write y=x2-4x+2k. And m:= (xm, ym) for the coordinates of our vertex. We deduce that xm is exactly the value of x for which y'=2x-4=0, because m is a minimum p...
Re arrange one of the equation to get a single variant answer. So, x = 12 - 3y. Substitute this into the other equation, so 3 (12-3y) + y = 8. Expand this equation to form 36 - 9y + y = 8. Collect the y t...
=(x+4)(x2+6x+5x+30)=(x+4)(x2+11x+30)=x3+11x2+30x+4x2+44x+120=x3+15x2+74x+120
Substitute y = 2x - 1 into the first equation.
2x + 3(2x -1) = 21
2x + 6x - 3 = 21
8x = 24
x = 3
Therefore y = 2(3) - 1 = 5
For convience we can call the polynomial f(x). Using the fact that the product of the roots of a polynomial equals the constant term, we know that the product of the roots is -15. We can therefore guess a...
←
442
443
444
445
446
→
Internet Safety
Payment Security
Cyber
Essentials